Human Interface and the Management of Information. Information and Knowledge Design and Evaluation 16th International Conference, HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014. Proceedings, Part I - Yamamoto, Sakae (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
The two-volume set LNCS 8521 and 8522 constitutes the refereed proceedings of the Human Interface and the Management of Information thematic track, held as part of the 16th International Conference on Human-Computer Interaction, HCII 2014, held in Heraklion, Greece, in June 2014, jointly with 13 other thematically similar conferences. The total of 1476 papers and 220 posters presented at the HCII 2014 conferences were carefully reviewed and selected from 4766 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems.The papers accepted for presentation thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. This volume contains papers addressing the following major topics: visualization methods and techniques; multimodal interaction; knowledge management; information search and retrieval; supporting collaboration; design and evaluation methods and studies.